2019
DOI: 10.1103/physrevlett.122.193901
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal-Space-Trajectory Perspective on High-Harmonic Generation in Solids

Abstract: We revisit the mechanism of high harmonic generation (HHG) from solids by comparing HHG in laser fields with different ellipticities but a constant maximum amplitude. It is shown that the cutoff of HHG is strongly extended in a circularly polarized field. Moreover, the harmonic yield with large ellipticity is comparable to or even higher than that in the linearly polarized field. To understand the underlying physics, we develop a reciprocal-space-trajectory method, which explains HHG in solids by a trajectory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 42 publications
(56 reference statements)
4
68
1
1
Order By: Relevance
“…Thus our findings confirm the very recently proposed four-step model of HHG in solids, i.e., before interband excitation (also be called "ionization") to the conduction band, the electron is accelerated for a while until it reaches to the top of the valence band [40]. It has been demonstrated that the cutoff of HHG is strongly extended in a circularly polarized field due to this preacceleration process [40]. Here we demonstrate that this preacceleration process has also consequences for linearly polarized two-color fields and results in a strong enhancement of the HHG and the population in the conduction band.…”
Section: Resultssupporting
confidence: 91%
“…Thus our findings confirm the very recently proposed four-step model of HHG in solids, i.e., before interband excitation (also be called "ionization") to the conduction band, the electron is accelerated for a while until it reaches to the top of the valence band [40]. It has been demonstrated that the cutoff of HHG is strongly extended in a circularly polarized field due to this preacceleration process [40]. Here we demonstrate that this preacceleration process has also consequences for linearly polarized two-color fields and results in a strong enhancement of the HHG and the population in the conduction band.…”
Section: Resultssupporting
confidence: 91%
“…Graphene is also convenient to integrate with other optical nanodevices thanks to its dimensionless and flexible properties [6]. Moreover, graphene is utilized to investigate nonlinear optics due to its high nonlinear coefficient [19][20][21][22][23]. Many schemes are proposed to manipulate the optical property and control the propagation of SPPs, such as coupled graphene waveguides [24][25][26], graphene metamaterials [7,27], and dynamic modulation [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Strong coupling can also lead to new series of energy conversion processes, such as the photon-thermal-electricity [107] and photon-electricity-thermal [108] processes induced by surface plasmon elements. This has opened up a new route for further exploration of the physical mechanism [109] of surface plasmon and exciton coupling and for the development of new optoelectronic devices, which will have great scientific significance.…”
Section: Conclusion and Development Trendsmentioning
confidence: 99%